Development of a recombinant (rOMP36) vaccine from Pasteurella multocida A:1 against pasteurellosis in chickens and ducks - Handijatno, Didik (2011)
Fowl cholera is one of the diseases that cause economic losses in poultry farms. It is caused by Pasteurella multocida serotype A in chickens but in ducks, it is caused by Riemerella anatipestifer or P. multocida serotype A or both. P. multocida serotype A:1 is highly virulent and is the common cause of the disease. Commercial vaccine is available for control but the vaccine provides homologous protection with limited cross-protection. Therefore, this study was conducted to identify suitable vaccine candidate for development of an improved vaccine against avian pasteurellosis. The study concentrated on the outer membrane proteins (OMPs) since OMPs play key roles in disease pathogenesis as well as in inducing immunity. Characterisation study on the OMPs of the various isolates of P. multocida serotypes A:1, A:3, A:1,3 and R. anatipestifer revealed that the major protein of P. multocida was 36 kDa while R. anatipestifer was 34.5 kDa. There were some differences among the OMPs of different serotypes of P. multocida, particularly in the minor bands where P. multocida serotype A:1,3 had more bands than other serotypes. Western blotting and immune-detection using antisera of rabbit against OMP 36 kDa and whole cell of P. multocida serotype A:1, revealed that the 36 kDa OMP of all serotypes of P. multocida and the 34.5 kDa OMP of R. anatipestifer appeared thick and dense. However, the 36 kDa OMP of P. multocida serotype A:1 appeared antigenic and provided cross-reaction with P. multocida serotypes A:3, A:1,3 and against R. anatipestifer. Therefore, the gene encoding 36 kDa OMP of P. multocida serotype A:1 was amplified by PCR before it was cloned in pET32 KL/LIC vector. The recombinant was successfully transformed into Escherichia coli Nova Blue strain as cloning host. Furthermore, the product was successfully sequenced and transformed into E. coli strain BL21 (DE3) and Origami2 (DE3) as expression host cells, revealing a single band of 1250 bp that consisted of 1050 bp gene insert and 200 bp pET32 vector. The sequence showed 100% homology to OMPH gene of P. multocida serotype A:1 and 99% to OMP H gene of P. multocida strain 18 and the OMP H of P. multocida subsp gallicida. The expressed protein was successfully verified by SDS-PAGE revealing the expected 40 kDa band. The recombinant of OMP36 gene was eventually prepared as killed bacteria or inoculums and injected intramuscularly into chickens and ducks before being challenged. The chickens and ducks received 0.5 mL of the inoculums containing 1.2x107CFU/mL. Following inoculation, antibody started to increase at week 1 and continued to increase after booster vaccination and reached peak at week 4 for both recombinant and commercial vaccines although the recombinant stimulated higher level of antibody compared to the commercial vaccine. Following challenge, the recombinant vaccine provided excellent protection homologous (21/25; 84%) and cross-protection against P. multocida serotype A:1,3 (23/25; 92%) but provided low cross-protection against P. multocida serotype A:3 (11/25; 44%) in chickens. In ducks, the recombinant provided moderate protection (14/25; 56%) compared to the excellent protection provided by the commercial vaccine (23/25; 92%). In conclusion, the recombinant vaccine generally provided better protection against the various serotypes of P. multocida than the commercial vaccine in chickens but less protection in ducks compared to the commercial vaccine.